Combinación económica financiera de policultivo ciclo corto y perenne en el cantón Balzar Provincia del Guayas. - Bone Castillo, Geovanna Gissela (2015)
Polyculture or associations of culture is regarded as the type of multiple crops on one hectare of land surface or to some like organic or natural agro point. Importantly, in our country there is a greater number of hectares planted with traditional methods ie monocultures, which often does not meet the economic expectations of small farmers. In Ecuador there is a greater management of aquiculture you polyculture farming. Several studies have greater advantages polycultures than monocultures such as greater control of pests and diseases, shade management, harnessing energy and soil nutrients among others. However it is vital to know the technical management of various crops set to ensure with this profitable crop quality. The major goal of this study is to determine whether there is an economic return when investing in establishing polyculture. For achieving this objective various procedures they were used to determine whether performance such as; production costs of various crops studied through surveys to know the technical crop management made by small producers to establish last point if there is a net benefit in this investigation, all this by Net (NPV) Present Value and Internal Rate of return (IRR) and according to the values presented in results and conclusions of that investment research is profitable because it generates an economic return which benefits producers who decide to invest in some kind of polyculture.